The impact of radiation therapy sequencing on survival and cardiopulmonary mortality in the combined modality treatment of patients with esophageal cancer. Issue 11 (7th February 2013) - Wojcieszynski, Andrzej P.; Berman, Abigail T.; Wan, Fei; Plastaras, John P.; Metz, James M.; Mitra, Nandita; Apisarnthanarax, Smith
Abstract : BACKGROUND: The addition of chemoradiation (CRT) to surgery has been shown to improve survival in patients with esophageal cancer. In the current study, the authors determined whether the sequencing of CRT has an effect on survival and cardiopulmonary mortality in patients with esophageal cancer. METHODS: Patients with the following inclusion criteria were identified within 17 Surveillance, Epidemiology, and End Results registries from 1988 through 2007: adenocarcinoma or squamous cell carcinoma of the esophagus and having undergone esophagectomy. Patients who died within 90 days of surgery were excluded. Demographic, tumor, and survival data were compared between patients receiving preoperative and postoperative RT. Cox proportional hazards regression models were calculated to identify parameters associated with cause‐specific survival and overall survival. A competing risk analysis was performed to account for death due to esophageal cancer in the calculation of cardiopulmonary mortality. RESULTS: Of 5512 patients, 1881 received preoperative RT, 901 received postoperative RT, and 2730 did not receive RT. Patients receiving preoperative RT had improved 5‐year cause‐specific survival (41% vs 31%; P < .0001) and overall survival (33% vs 23%; P < .0001) compared with those receiving postoperative RT. No differences in adjusted cardiopulmonary mortality were found between patients who received RT versus those who did not (8% vs 10% at 10 years; hazards ratio [HR], 0.84 [95% confidence interval (95% CI), 0.64‐1.12] [ P = .24]) or between those treated with preoperative RT versus those treated with postoperative RT (HR, 0.70; 95% CI, 0.46‐1.08 [ P = .11]). CONCLUSIONS: These population‐based data support the use of preoperative RT in patients with locally advanced esophageal cancer. RT should not be withheld out of concern for cardiopulmonary mortality. Cancer 2013;119:1976–1984. © 2013 American Cancer Society.